logo for solving-math-problems.com
leftimage for solving-math-problems.com

Expression help - Solve Equation

by Amanda
(PA)











































Solve the following equation for Z

22 = -Z + (-9)

I have no idea how to do this!

Comments for Expression help - Solve Equation

Click here to add your own comments

Oct 05, 2011
Solve Equation
by: Staff


Question:

by Amanda
(PA)


22 = -Z + (-9)

I have no idea how to do this!



Answer:

22 = -Z + (-9)

22 + Z = -Z + (-9) + Z

22 + Z = -Z + Z + (-9)

22 + Z = 0 + (-9)

22 + Z = -9

22 - 22 + Z = -9 - 22

0 + Z = -9 - 22

Z = -9 - 22

Z = -31


Check the answer by substituting -31 for Z in the original equation

22 = -Z + (-9)

22 = -(-31) + (-9)

22 = [(-1) * (-31)] + (-9)

22 = [31] + (-9)

22 = 31 + (-9)

22 = 31 - 9

22 = 22, OK → Z = -31 is a valid solution





Thanks for writing.

Staff
www.solving-math-problems.com


Click here to add your own comments

Join in and write your own page! It's easy to do. How? Simply click here to return to Math Questions & Comments - 01.



Copyright © 2008-2015. All rights reserved. Solving-Math-Problems.com